Aging and Mitochondrial DNA - Das, P.; Guha, G. (Journal of Scientific Research, 2010)
According to the mitochondrial theory of aging, accrual of mutations in mitochondrial DNA (mtDNA) plays the paramount function in the cellular pathology of aging and in development of age-related degenerative ailments. Reactive oxygen species (ROS), which are byproducts of oxidative phosphorylation (OX-PHOS) in aerobic (mitochondrial) respiration, cause oxidative stress-induced damage to mtDNA. This damaged DNA, whose normal role is to encode proteins many of which are players in the electron transport chain (ETC), now codes for defective proteins. Such faulty proteins lead to a considerable impairment in the efficacy of ETC, thereby generating more ROS, which cause further damage to mtDNA in turn, leading to further defects in proteins, aggravated ETC dysfunction, and even more ROS. Hence, a ‘vicious cycle’ propagates that ultimately directs tissue cells towards structural and functional decline, or in other words, degeneration and aging. However, in spite of a wide acceptance of this theory, there have simultaneously been a considerable number of criticisms against it. This review is aimed at discussing the paradigm of aging and degenerative diseases in light of the mitochondrial paraphernalia, with reference to the evidences in support as well as in antagonism to the mitochondrial theory of aging. Keywords: Aging; Degenerative diseases; mtDNA mutations; ROS; Cell death. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.5078 J. Sci. Res. 3 (1), 176-186 (2011)